Acquisition of discourse markers - evidence from EFL Writing - Mihaljević-Djigunović, Jelena (Array, 2010)
The paper focuses on a mixed-method study aimed at investigating Croatian primary and secondary school students´ use of English discourse markers in written language production. The results of the study, carried out on a sample of 200 participants, indicate that Croatian EFL learners have a relatively poor command of English discourse markers at both proficiency levels. The results suggest that they tend to use a relatively small range of English discourse markers and point to L1 interference and inadequate input as possible causes of low acquisition of English discourse markers.